Pengembangan Modul Pembelajaran Inovatif Untuk Pendidikan Vokasional Agribisnis Di Sekolah Menengah Kejuruan - Edi Sulaiman; Yunita Widia Putri; Nurlina Wahyuningsih; Sa’idy (CV. Creative Tugu Pena, 2022)
The quality of vocational education, particularly in the agribusiness sector at vocational high schools (SMK), is still facing several challenges, including the limited use of contextual and innovative learning materials that align with industry demands. Learning modules currently in use tend to be theoretical, less interactive, and do not adequately support students' practical skills or entrepreneurship development. This research aims to develop an innovative learning module to enhance the effectiveness and relevance of teaching agribusiness in SMKs. The study employs a Research and Development (R&D) approach, adapted from the Borg and Gall model, involving stages of needs analysis, design, development, expert validation, revision, limited trial, and broader field testing. Data were collected through interviews, observations, questionnaires, expert validations, and student learning outcomes (pretest and posttest). The module was developed using a combination of Problem-Based Learning (PBL), Project-Based Learning (PjBL), and Teaching Factory approaches, and integrated with digital media and interactive content. The results show that the module is valid according to experts in terms of content, language, and presentation, and is practical and effective based on responses from teachers and students. The implementation of the module in classrooms improved student engagement, collaboration, and achievement. Furthermore, students demonstrated better understanding of agribusiness concepts and improved entrepreneurial skills. In conclusion, the development of this innovative learning module provides a significant contribution to improving the quality of vocational agribusiness education and can serve as a model for future instructional material design in similar contexts